Identification and Optimisation of Lipase-Catalysed Synthesis of Betulinic Acid Amide in a Solvent System. (17th July 2016) - Atikah Binti Amin Yusof, Nurul; Mat Hadzir, Nursyamsyila; Efliza Ashari, Siti
Abstract : Betulinic acid amide was synthesized from the enzymatic reaction of betulinic acid and butylamine catalysed by Novozym 435. The effects of different reaction parameters, such as effect of reaction time, reaction temperature, amount of enzyme, and substrate molar ratio (betulinic acid : butylamine), were studied and conventionally optimised. Based on this study, the enzymatic synthesis of betulinic acid amide was found to be 64.6% at the optimum conditions of 24 h, 40°C, 100 mg enzyme, and 1 : 1 substrate molar ratio in 9 : 1 mixture of chloroform and hexane as solvent. The identification of final product was carried out using TLC, melting point, and FTIR and NMR showed the presence of betulinic acid amide.